2008
DOI: 10.31420/uakari.v3i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Da Construção Da Rodovia Pa-458 Sobre as Florestas De Mangue Da Península Bragantina, Bragança, Pará, Brasil

Abstract: The PA-458 highway construction caused severe impact on mangrove Forest in the Ajuruteua peninsula, Bragança-PA, mainly at the Km 17. In order to better understand the effect of the highway construction on mangrove forest, it was undertaken a phytographic profile and a study on the structure of mangrove stands under three different levels of environmental destruction: Degraded Area (DA), Semi-Degraded Area (SDA), and Non-Degraded Area (NDA). Considering the three levels of destruction, mangrove stands comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
7
0
5
Order By: Relevance
“…It is important to note that the construction in the 1970s of the PA-458 state highway, which connects Bragança to the village of Ajuruteua, bisected 26 km of the local mangrove forest [10], and impacted an area of 3.8 km 2 of this ecosystem [19]. These authors concluded that he primary source of this impact was the obstruction of the tidal creeks on the east of the peninsula, that drain into the Caeté River.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that the construction in the 1970s of the PA-458 state highway, which connects Bragança to the village of Ajuruteua, bisected 26 km of the local mangrove forest [10], and impacted an area of 3.8 km 2 of this ecosystem [19]. These authors concluded that he primary source of this impact was the obstruction of the tidal creeks on the east of the peninsula, that drain into the Caeté River.…”
Section: Study Sitementioning
confidence: 99%
“…In Brazil, the exploitation of these systems has involved even more drastic impacts, such as the installation of shrimp farms at many locations in the northeast of the country [8], deforestation and lumbering in the southeast [9], and the construction of highways in the extreme north [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro lado, a história da construção da rodovia PA-458 evidencia o lugar da natureza nos projetos de desenvolvimento desse período. Estudos sobre os impactos socioambientais do aterramento de 26km de manguezais só começaram a ser feitos a partir da década de 1990 (Maneschy, 1993a) e com maior intensidade nos anos 2000 (Carvalho, 2000;Fernandes et al, 2007;Nascimento, 2008). Com a inauguração da estrada, o fluxo de turistas na praia de Ajuruteua aumentou, mas, sendo feito de modo desordenado e sem políticas de inclusão da comunidade local, o turismo levou consigo o problema do lixo, a especulação imobiliária, o encarecimento dos produtos no comércio e o crescimento demográfico igualmente desordenado.…”
Section: Considerações Finaisunclassified
“…O problema é que, no meio do caminho, havia um mangue. O município de Bragança está inserido na região que detém uma das maiores reservas de manguezais do mundo (Fernandes, 2003) nas latitudes próximas à linha do Equador, litoral amazônico, entre a foz do rio Oiapoque (no Amapá) e a baía de São Marcos (no Maranhão), área conhecida como "costa norte".…”
unclassified